2021
DOI: 10.1093/mnras/stab3544
|View full text |Cite
|
Sign up to set email alerts
|

Unequal-mass mergers of dark matter haloes with rare and frequent self-interactions

Abstract: Dark matter self-interactions have been proposed to solve problems on small length scales within the standard cold dark matter cosmology. Here we investigate the effects of dark matter self-interactions in merging systems of galaxies and galaxy clusters with equal and unequal mass ratios. We perform N-body dark matter-only simulations of idealised setups to study the effects of dark matter self-interactions that are elastic and velocity-independent. We go beyond the commonly adopted assumption of large-angle (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…4). It is also worth mentioning, that we found earlier, in a study of head-on collisions of unequal mass mergers (Fischer et al 2021b), that fSIDM subhaloes dissolve faster than rSIDM subhaloes when they are matched in terms of 𝜎T/𝑚 𝜒 .…”
Section: Halo and Subhalo Mass Functionmentioning
confidence: 66%
See 1 more Smart Citation
“…4). It is also worth mentioning, that we found earlier, in a study of head-on collisions of unequal mass mergers (Fischer et al 2021b), that fSIDM subhaloes dissolve faster than rSIDM subhaloes when they are matched in terms of 𝜎T/𝑚 𝜒 .…”
Section: Halo and Subhalo Mass Functionmentioning
confidence: 66%
“…Depending on the cross-section this can give more stringent limitations on the time step than imposed by the gravity scheme. We found that the time-step criterion introduced by Fischer et al (2021b) for velocity-independent self-interactions is not always well-suited for a velocity-dependent cross-section (this has been previously described by Kasselmann 2021). Here we introduce a new time step criterion for velocity-dependent scattering that has a velocity-dependence as described by Eq.…”
Section: Time Step Criterionmentioning
confidence: 82%
“…In the literature various methods have been applied to measure shapes (e.g. Allgood et al 2006;Bett et al 2007;Warnick et al 2008;Bett 2012;Schneider et al 2012;Peter et al 2013;Robertson et al 2019;Banerjee et al 2020;Chua et al 2021;Sameie et al 2018;Fischer et al 2021a;Harvey et al 2021;Vargya et al 2022). An overview of different methods is given by Zemp et al (2011).…”
Section: Measuring Shapesmentioning
confidence: 99%
“…The identification and characterization of cluster substructures is important in many ways. It allows us to test the cosmological model of halo assembly (e.g., Richstone et al 1992;Mohr et al 1995;Thomas et al 1998;Suwa et al 2003;Prokhorov & Durret 2007;Forero-Romero et al 2010;Asencio et al 2021), to improve our understanding of the evolutionary mechanisms of galaxies in high-density regions (e.g., Bekki 1999;Dubinski 1999;Gnedin 1999;Poggianti et al 2004;Tonnesen & Bryan 2008;Mahajan 2013;Ribeiro et al 2013b;Olave-Rojas et al 2018;Bellhouse et al 2022), to constrain the nature of dark matter (DM; see e.g., Markevitch et al 2004;Clowe et al 2006;Merten et al 2011;Fischer et al 2022), and to identify clusters with an unrelaxed dynamical status caused by mergers, which can lead to biased estimates of the cluster mass (e.g., Motl et al 2005;Biviano et al 2006;Ventimiglia et al ⋆ E-mail: jose.benavides@unc.edu.ar 2008; Takizawa et al 2010;Angrick & Bartelmann 2012;Barrena et al 2013;Laganá et al 2019;Zhang et al 2022).…”
Section: Introductionmentioning
confidence: 99%